The time-dependent changes in serum immunoglobulin after kidney transplantation and its association with infection - Jo, Eun-Ah; Min, Sangil; Jo, Ae jung; Han, Ahram; Ha, Jongwon; Song, Eun Young; Lee, Hajeong; Kim, Yong Chul (Frontiers in Immunology, 2024)
In this study, we aimed to analyze the time-dependent changes in serum immunoglobulin and complement levels in kidney transplant recipients and determine the risk factors associated with infection. A retrospective analysis of serum samples from 192 kidney transplant recipients from August 2016 to December 2019 was conducted, with samples obtained at preoperative baseline (T0), postoperative 2 weeks (T1), 3 months (T2), and 1 year (T3), and analyzed for serum C3, C4, IgG, IgA, and IgM. The results revealed that at 2 weeks post-transplantation (T1), IgG and IgA levels significantly decreased, and hypogammaglobulinemia (HGG) and hypocomplementemia (HCC) were most common. The period following T1 also exhibited the highest incidence of severe infection requiring hospitalization and graft-related viral infection.In a time-dependent Cox proportional hazards model adjusted for time varying confounders, HGG was significantly associated with infection requiring hospitalization (HR 1.895, 95% CI 1.871-1.920, P-value<0.001) and graft-related viral infection (HR 1.152, 95% CI 1.144-1.160, P-value<0.001). In conclusion, monitoring serum immunoglobulin levels provides valuable insights into the degree of immunosuppression in transplant recipients, and HGG in the posttransplant period is identified as a risk factor for clinically significant infections, suggesting that serum immunoglobulins may serve as a feasible biomarker for infection risk in kidney transplant patients.